MODEL INTEGRASI ILMU DAN PENGEMBANGANNYA DI FAKULTAS SYARI’AH DAN HUKUM UIN AR-RANIRY BANDA ACEH DAN UIN SUMATERA UTARA - Tarmizi M Jakfar; Fuad Ramly; Maimun Fuadi; Jabbar Sabil (Universitas Islam Negeri Ar-Raniry, 2019)
Integration of science is a central issue in the arena of the State Islamic University (UIN) in Indonesia, including UIN Ar-Raniry and UIN North Sumatra. One of the main problems that is increasingly discourse is the model of the integration of knowledge that is put in place and the development efforts implemented. Although UIN Ar-Raniry has an integration model of